Home gardens, dietary diversity and household food security in urban informal settlements in Kisumu, Kenya - Musita, Consolata; Ngala, Sophia; Abong, George; Akingbemisilu, Tosin; Chege, Christine; Termote, Celine (2024)
Malnutrition ▪Sub-SaharanAfrica (SSA) is experiencing triple burden of malnutrition (Global nutrition report, 2020) ▪Non-communicable diseases (NCDs) are also an emerging global health threat (WHO, 2023) ▪The statistics are same in Kenya (KDHS,2023)